MUHAMMAD IBN ABD AL-RAHMAN (STUDI ATAS PERANANNYA DALAM PENGEMBANGAN FILSAFAT DAN SAINS DI ANDALUSIA) - Anastya Nida Alhana (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
Muhammad Ibn Abd Rahman is known as Muhammad I was the 5th emir during the reign of the Umayyad Dynasty in Spain in 852-886 AD. He was the son of Abdurrahman Bin Hakam a 4th leader of the Umayyad Dynasty in Spain. He died at the age of 65 years coinciding in 886 AD and at the end of his term of office. The beginning of Muhammad I is served as a series of domestic riots. The government shock is began with the Toledo People’s rebellion, assisted by the Leon tribal chief to rebel in 854 AD, As an emir who was an expert in the administration of his government, he is organized the Andalusian government on a regular basis and created a system of government regulations in the form of legislation. For the management of the State, he also carries out government policies that lead to the welfare of people’s lives. Like his father, one of his personalities was to love the art of beauty and science, so that during his reign he built the city by beautifying the capital city with beautiful buildings, large buildings, and monuments, and he was a supporter of the facilities for education, as well as poets and writers also got their attention. His great contribution in advancing Spanish civilization, which is someone who initiated the growth of progress in the field of Islamic Philosophy and Science in Spain, has recorded one sheet of culture in the achievement of Islamic history. The interest in Greek Philosophy and Science began to be developed in the 9th century AD during the reign of the fifth Umayyad, namely Muhammad Ibn Abd al-Rahman (832-886 AD) at the initiative of al-Hakam (961-976 AD), the scientific works, libraries and universities are able to rival Baghdad as the main center of science in the Islamic world.